Artificial Life—Artificial Personality - Ken Kaplan; Ted Krueger (Oz, 1993)
The position of the architect in contemporary practice is a difficult one utilizing technologies that have remained essentially unchanged for decades to implement the program of those with power or money. Are you excited yet? Many have found solace in the evolutionary development of that perfect roofing detail, or in the latest formal gymnastic, or theoretical convolution.